2017
DOI: 10.1038/s41598-017-02697-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-150 modulates intracellular Ca 2+ levels in naïve CD8+ T cells by targeting TMEM20

Abstract: Regulation of intracellular Ca2+ signaling is a major determinant of CD8+ T cell responsiveness, but the mechanisms underlying this regulation of Ca2+ levels, especially in naïve CD8+ T cells, are not fully defined. Here, we showed that microRNA-150 (miR-150) controls intracellular Ca2+ levels in naïve CD8+ T cells required for activation by suppressing TMEM20, a negative regulator of Ca2+ extrusion. miR-150 deficiency increased TMEM20 expression, which resulted in increased intracellular Ca2+ levels in naïve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The next step will logically be to use this knowledge in order to target SOCE, and thus treat human patients afflicted with diseases linked to SOCE aberrant activity. In a recent study, miR-150 was shown as an endogenous inhibitor of POST, important for CD 8+ T cells activation [96]. According to this work, targeting of SOCE partner protein POST with miR-150 could therefore represent a new treatment against auto-immune diseases.…”
Section: Capacitative Calcium Entry (Cce) and Associated Proteinsmentioning
confidence: 82%
“…The next step will logically be to use this knowledge in order to target SOCE, and thus treat human patients afflicted with diseases linked to SOCE aberrant activity. In a recent study, miR-150 was shown as an endogenous inhibitor of POST, important for CD 8+ T cells activation [96]. According to this work, targeting of SOCE partner protein POST with miR-150 could therefore represent a new treatment against auto-immune diseases.…”
Section: Capacitative Calcium Entry (Cce) and Associated Proteinsmentioning
confidence: 82%
“…Since this is essential to induce the expression of activation-associated genes, miR-150-induced reduction in TMEM20 allows naïve CD8 + T cells to express anergy-inducing genes, such as Casitas B lineage lymphoma b (Cbl-b), Egr2 and p27. These findings suggest the central role of TCR-mediated intracellular Ca 2+ regulation in naïve CD8 + T cells [72].…”
Section: Stim1 Scaffold Proteinsmentioning
confidence: 72%
“…It is proved that this effect depends on the regulation of Myc and Bcl-2 by miR150 (1). These studies reveal that miR150 relates to the development, maturity, and cytotoxicity of NK cells (9). In our study, if NK cells had miR150 reduction, the function for disturbing target cells of NK cells would be enhanced.…”
Section: Discussionmentioning
confidence: 99%